2005
DOI: 10.1111/j.1365-2591.2005.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Defects in ProTaper S1 instruments after clinical use: longitudinal examination

Abstract: Multiple use of ProTaper S1 pre-disposed the instrument to microcrack formation and wear of the cutting edges. There was a low prevalence of plastic deformation and most ProTaper S1 instruments failed without discernible sign of unwinding of the flutes. Further studies should address the mode of failure and the role of debris particles in the fracture mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 25 publications
5
83
0
8
Order By: Relevance
“…Blunt cutting edges were also observed in this present study on all new and used files, as reported by Eggert et al (4) , who also found them on new and used instruments. After a full clean with ultrasound bath and a sterilisation technique, on all ProTaper files, dentine remnants were found on the cutting edges, they were also found trapped in fatigue cracks as described by other authors (11). Sterilization of previously used files is not 100% Foot note: (1) and (2): different SX and S1 files used.…”
Section: Discussionmentioning
confidence: 78%
“…Blunt cutting edges were also observed in this present study on all new and used files, as reported by Eggert et al (4) , who also found them on new and used instruments. After a full clean with ultrasound bath and a sterilisation technique, on all ProTaper files, dentine remnants were found on the cutting edges, they were also found trapped in fatigue cracks as described by other authors (11). Sterilization of previously used files is not 100% Foot note: (1) and (2): different SX and S1 files used.…”
Section: Discussionmentioning
confidence: 78%
“…The S1 instrument has a small and thin tip. If this tip should become engaged in a constricted lumen, the stress that builds up may quickly exceed the ultimate strength of such a small piece of material, thus leading the fracture (17).…”
Section: Discussionmentioning
confidence: 99%
“…The development of visible alterations in flute pitch and helical angle during instrumentation procedures is beneficial in alerting practitioners to discard files before fracture (110). The ProFile Vortex file appears less likely to produce such deformations, and separation might occur without warning.…”
Section: Clinical Applicationsmentioning
confidence: 99%